Lysosomal Cathepsin A Plays a Significant Role in the Processing of Endogenous Bioactive Peptides - Timur, Zehra Kevser; Akyildiz Demir, Secil; Seyrantepe, Volkan (Frontiers in Molecular Biosciences, 2016)
Lysosomal serine carboxypeptidase Cathepsin A (CTSA) is a multifunctional enzyme with distinct protective and catalytic function. CTSA present in the lysosomal multienzyme complex to facilitate the correct lysosomal routing, stability and activation of with beta–galactosidase and alpha-neuraminidase. Beside CTSA has role in inactivation of bioactive peptides including bradykinin, substances P, oxytocin, angiotensin I and endothelin-I by cleavage of 1 or 2 amino acid(s) from C-terminal ends. In this study, we aimed to elucidate the regulatory role of CTSA on bioactive peptides in knock-in mice model of CTSAS190A. We investigated the level of bradykinin, substances P, oxytocin, angiotensin I and endothelin-I in the kidney, liver, lung, brain and serum from CTSAS190A mouse model at 3- and 6-months of age. Our results suggest CTSA selectively contributes to processing of bioactive peptides in different tissues from CTSAS190A mice compared to age matched WT mice.